Decadal Response of Mesozooplankton Assemblages to Nutrient Load Reductions in Laizhou Bay, China - Jiang, Huichao; Liu, Dongyan; Ma, Yuanqing; Su, Bo; Liu, Ning; Zhang, Juan; He, Jianlong; Qin, Huawei; Song, Xiukai; Sun, Shan; Xing, Hongyan (Frontiers in Marine Science, 2022)
Reducing nutrient loads from catchments is an important strategy to mitigate coastal eutrophication. The decadal responses of ecosystems to nutrient load reductions can help us understand the effectiveness of environmental restoration. Here, the cascading trophic interactions of mesozooplankton and phytoplankton in Laizhou Bay were analyzed to examine the effects of nutrient load reductions from rivers during 2004–2014. The results showed that the diversity of the mesozooplankton assemblages and the proportion of higher trophic species increased after nutrient load reductions, and mesozooplankton abundance showed an obviously decreasing annual trend. A significantly positive correlation between mesozooplankton and phytoplankton abundance was identified for August. Mesozooplankton abundance was mainly influenced by phytoplankton abundance in August, but by microzooplankton prey or jellyfish predators in May when phytoplankton abundance was low. This result indicates that the recovery of mesozooplankton assemblages in Laizhou Bay is a slow process after nutrient load reductions and might have cascading trophic interactions with phytoplankton recovery.